Innovative strategies targeting oral microbial dysbiosis: unraveling mechanisms and advancing therapies for periodontitis - Li, Yang; He, Xinyu; Luo, Guocheng; Zhao, Juanjuan; Bai, Guohui; Xu, Delin (Frontiers in Cellular and Infection Microbiology, 2025)
Periodontitis, a prevalent inflammatory oral disease, is intricately linked to disruptions in the oral microbiome, a state known as microbial dysbiosis. This review explores the pivotal roles of key pathogens, including Porphyromonas gingivalis and Tannerella forsythia, in driving periodontitis and examines the underlying molecular mechanisms that disrupt microbial homeostasis. We discuss how interactions among bacterial species affect the oral ecosystem’s balance and how microbial metabolites influence the host immune responses, contributing to disease progression. Leveraging these insights, we propose cutting-edge therapeutic approaches aimed at restoring microbial equilibrium. These include personalized pharmacological interventions tailored to individual microbiome profiles and innovative microbiome-targeted strategies such as probiotic formulations and bacteriophage therapy. By precisely modulating microbial communities, these strategies hold promise for enhancing treatment efficacy, preventing disease recurrence, and mitigating issues like antimicrobial resistance. Overall, this review paves the way for novel prevention and management techniques in periodontitis, offering significant improvements in oral health outcomes for patients.